Methods of crop improvement and applications towards fortifying food security - Patel, Aayushi; Miles, Andrew; Strackhouse, Tara; Cook, Logan; Leng, Sining; Patel, Shrina; Klinger, Kelsey; Rudrabhatla, Sairam; Potlakayala, Shobha D. (Frontiers in Genome Editing, 2023)
Agriculture has supported human life from the beginning of civilization, despite a plethora of biotic (pests, pathogens) and abiotic (drought, cold) stressors being exerted on the global food demand. In the past 50 years, the enhanced understanding of cellular and molecular mechanisms in plants has led to novel innovations in biotechnology, resulting in the introduction of desired genes/traits through plant genetic engineering. Targeted genome editing technologies such as Zinc-Finger Nucleases (ZFNs), Transcription Activator-Like Effector Nucleases (TALENs), and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) have emerged as powerful tools for crop improvement. This new CRISPR technology is proving to be an efficient and straightforward process with low cost. It possesses applicability across most plant species, targets multiple genes, and is being used to engineer plant metabolic pathways to create resistance to pathogens and abiotic stressors. These novel genome editing (GE) technologies are poised to meet the UN’s sustainable development goals of “zero hunger” and “good human health and well-being.” These technologies could be more efficient in developing transgenic crops and aid in speeding up the regulatory approvals and risk assessments conducted by the US Departments of Agriculture (USDA), Food and Drug Administration (FDA), and Environmental Protection Agency (EPA).